Analisa Metode Association Rule Untuk Penjualan Skincare Menggunakan Algoritma Pincer Serach - Nadia Indah Tarakanita; Yusni Amaliah; Anto, Anto (Journal of Big Data Analytic and Artificial Intelligence, 2023)
Rumah Masker Tarakan is a business entity in the field of selling cosmetic and skincare products. A common problem faced by Rumah Masker is the placement of products, which often leads to difficulties in finding similar products. Therefore, a method is needed to organize the layout of skincare products that are frequently purchased together, making it easier for customers to select the products they want. The Pincer Search Algorithm, also known as the Two-Way Search, uses two approaches: Top-Down and Bottom-Up. In its process, the primary direction of the Pincer Search is Bottom-Up. The Maximum Frequent Set is a collection of maximal itemsets that are classified as frequent. The purpose of the Maximum Frequent Set is to reduce (prune) the number of candidate Frequent Itemsets that need to be examined in the Bottom-Up process. Based on research conducted using the Pincer Search Algorithm with sales data from January to June 2022, involving a total of 148 data points, it was found that 72 transactions yielded a value of 0.028% for a candidate of 3 itemsets. This demonstrates that the best sales performance occurs with a combination of 3 itemsets.